Multi-omics approach reveals the contribution of OsSEH1 to rice cold tolerance - Gu, Shuang; Zhuang, Jia; Zhang, Zhe; Chen, Wanchun; Xu, Hai; Zhao, Minghui; Ma, Dianrong (Frontiers in Plant Science, 2023)
As low environmental temperature adversely affects the growth, development and geo-graphical distribution, plants have evolved multiple mechanisms involving changing physiological and metabolic processes to adapt to cold stress. In this study, we revealed that nucleoporin-coding gene OsSEH1 was a positive regulator of cold stress in rice. Physiological assays showed that the activity of antioxidant enzymes showed a significant difference between osseh1 knock-out lines and wild type under cold stress. Metabolome analysis revealed that the contents of large-scale flavonoids serving as ROS scavengers were lower in osseh1 mutants compared with wild type under cold stress. Transcriptome analysis indicated that the DEGs between osseh1 knock-out lines and wild type plants were enriched in defense response, regulation of hormone levels and oxidation-reduction process. Integration of transcriptomic and metabolic profiling revealed that OsSEH1 plays a role in the oxidation-reduction process by coordinately regulating genes expression and metabolite accumulation involved in phenylpropanoid and flavonoid biosynthetic pathway. In addition, Exogenous ABA application assays indicated that osseh1 lines had hypersensitive phenotypes compared with wild type plants, suggesting that OsSEH1 may mediate cold tolerance by regulating ABA levels.